Transformasi Organisasi, Kepemimpinan Transformasional dan Perubahan Peran Sumber Daya Manusia - Susilawati, C. Erna (Fakutas Ekonomi Unika Widya Mandala Surabaya, 2004)
Continuously changing environmental conditions, globalization, technology developments and increasingly hard competition has made companies b rake measures lo survive. It needs organizational transformation that allows it to become more flexible and able to detect the changes immediately and mal